2(q+2)+3=w

Simple and best practice solution for 2(q+2)+3=w equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(q+2)+3=w equation:


Simplifying
2(q + 2) + 3 = w

Reorder the terms:
2(2 + q) + 3 = w
(2 * 2 + q * 2) + 3 = w
(4 + 2q) + 3 = w

Reorder the terms:
4 + 3 + 2q = w

Combine like terms: 4 + 3 = 7
7 + 2q = w

Solving
7 + 2q = w

Solving for variable 'q'.

Move all terms containing q to the left, all other terms to the right.

Add '-7' to each side of the equation.
7 + -7 + 2q = -7 + w

Combine like terms: 7 + -7 = 0
0 + 2q = -7 + w
2q = -7 + w

Divide each side by '2'.
q = -3.5 + 0.5w

Simplifying
q = -3.5 + 0.5w

See similar equations:

| (2x^2+3x-1)x(x+1)= | | -6X+5Y=7 | | 3x=5y-15 | | y=16.5 | | 4z-9=5z | | -9(x+2)=-12x+3 | | X=y+y^2 | | 9x+12y=48 | | y=x+x^2 | | 22=-5v+9v | | 4+1.2x=0.3x+7 | | z^2=-8 | | 2x+-1=5 | | 7.2x=216 | | m+240=500 | | (3x-3)(x+6)=0 | | 2(x-4)=8x-11 | | 3(x^2-12x+36)=9 | | 9/10x=18 | | 30m+9-17m=48 | | 3x^2-3x=-5x+8 | | 2f+3=9 | | y=(2.5+-0.5y)-4 | | 2x-4y=90 | | 6(x+4)+2x=64 | | 3n-6+5n=4n-2(-2n-3) | | 7+5(3x-4)=7(x-1) | | u=5(4n+30)+8(n+1) | | 32-4n=56 | | x+0.41=1 | | 2.4x-6=1.4x+8 | | x+0.53=1 |

Equations solver categories